Augmented reality technology in a basic Chinese vocabulary course: a study in a Thai university - Pattanasak Muangchan; Zhao Yanhua (Cogent Education)
Augmented Reality (AR) impacts various aspects of life, including education. For instance, AR is beneficial for teaching Chinese vocabulary to second-language learners. The primary objective of this study was to compare the achievement of first-year General Education (GE) students in Thailand in learning basic Chinese vocabulary through Augmented Reality (AR) and to evaluate their overall satisfaction with the Augmented Reality (AR) learning experience. The research employed an experimental design, establishing causality with controlled conditions and systematic variable manipulation. Simple random sampling was utilized, involving 180 students aged 18 to 21 from diverse majors, including English, marketing, communication arts, medical technology, veterinary science, and pharmacy. Of these, 58 students participated, and the group was divided into experimental and control groups. The results indicated that using Augmented Reality (AR) for teaching Chinese vocabulary led to improved achievement and might enhance comprehension, memorability, and retention compared to traditional methods. Additionally, qualitative findings revealed opportunities and challenges associated with employing Augmented Reality (AR) in teaching and learning.